2017
DOI: 10.2486/indhealth.2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep disturbances and depression in daytime workers: a cross-sectional structured interview survey

Abstract: The aim of this study was to clarify the relationship between sleep disturbances and depression in daytime workers using a structured interview. A total of 1,184 daytime workers were enrolled. We evaluated difficulty initiating sleep (DIS), difficulty maintaining sleep (DMS), early morning awakening (EMA), and global insomnia scores (ISs) in all participants. As a result, the prevalences of DIS, DMS, and EMA were 16%, 46%, and 22%, respectively. IS was significantly correlated with depression score. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Moreover, our findings indicated that possible anxiety and possible depression more frequently occurred in participants with SOL + WASO + EMA-insomnia compared with SOLinsomnia. While this is somewhat in contrast with previous studies suggesting depression to be more strongly associated with early morning awakening (Rodin et al, 1988;Lustberg and Reynolds, 2000) or difficulty initiating sleep (Yokoyama et al, 2010;Ikeda et al, 2017), it is important to emphasize that previous studies did not include mixed insomnia subtypes. It can therefore not be ruled out that these studies would have provided similar results as the current study if they had also included combinations of the insomnia subtypes.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Moreover, our findings indicated that possible anxiety and possible depression more frequently occurred in participants with SOL + WASO + EMA-insomnia compared with SOLinsomnia. While this is somewhat in contrast with previous studies suggesting depression to be more strongly associated with early morning awakening (Rodin et al, 1988;Lustberg and Reynolds, 2000) or difficulty initiating sleep (Yokoyama et al, 2010;Ikeda et al, 2017), it is important to emphasize that previous studies did not include mixed insomnia subtypes. It can therefore not be ruled out that these studies would have provided similar results as the current study if they had also included combinations of the insomnia subtypes.…”
Section: Discussioncontrasting
confidence: 89%
“…Overall, the most logical approach would be to subtype according to specific sleep-related characteristics. Therefore, in the present study we divided insomnia into subtypes based on when the sleep difficulty was experienced during the night (sleep onset insomnia, sleep maintenance insomnia and early morning awakening insomnia) which as noted, represent subtypes previously described in the literature (Taylor et al, 2005;Pigeon, 2010;Yokoyama et al, 2010;Espie et al, 2012;Ikeda et al, 2017). Even though there exist some research on demographic characteristics associated with insomnia, there is a dearth of research on the distribution of insomnia subtypes within these characteristics.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this trial, early morning awakening is defined as the final morning awakening with a wake-up time ≥ 1 h prior to desired wake up time [14,24,25].…”
Section: Eligibility Criteriamentioning
confidence: 99%